Evaluation of the efficacy of hydrated sodium calcium aluminosilicate at mitigating the negative impact of aflatoxicosis on nutrient digestibility and other production- and health-related indices in broiler chickens - Ahmed Ali Saleh; Rashed A. Alhotan; Mohammed A.A. Al-Badwi; Elsayed Osman Hussein; Livio Galosi; Giuseppe Crescenzo; Mahmoud Alagawany; Walied Abdo; Sara Mahmoud Omar; Claudia Zizzadoro (Journal of Applied Poultry Research)
SUMMARY: Dietary supplementation with aluminosilicates is a field-practical and cost-effective strategy to reduce the toxicity of feedborne aflatoxins in poultry. Importantly, not all types of aluminosilicates have the same decontaminating efficiency; thus, a full characterization of the protective properties of each single material would assist in selecting the most appropriate binder. Hydrated sodium calcium aluminosilicate (HSCAS) has been proven protective against many of the deleterious effects produced by aflatoxin B1 (AFB1) in broiler chickens. However, to date, there is no information specifically concerning its ability to counteract AFB1-induced impairment of nutrient digestibility in these animals. Therefore, expanding on previous research, we sought to fill this gap by incorporating new analyses on nutrient digestibility in a typical panel of aflatoxicosis-relevant endpoints. The aflatoxicated chickens that did not receive HSCAS showed many of the commonly reported signs of aflatoxicosis, including growth depression, liver injury, impaired immune function. Interestingly, some less common aflatoxicosis manifestations were also observed, such as increased serum glucose and cholesterol levels, and increased relative weight of abdominal fat. An unexpectedly low sensitivity to the challenge with AFB1 was recorded for the digestibility-related parameters. In AFB1-exposed chickens that received HSCAS, most of the abovementioned signs of aflatoxicosis were not observed, and the few still-occurring ones were substantially mitigated. Interestingly, some of the production- and health-related variables investigated showed significant improvement even when compared with control chickens. Overall, this study brings new knowledge regarding the potential manifestations of aflatoxicosis in broiler chickens and spectrum of HSCAS' beneficial effects, thereby contributing to better identification and control of an aflatoxin problem in poultry farms.